2020
DOI: 10.1038/s41598-020-68577-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased temperature has no consequence for behavioral manipulation despite effects on both partners in the interaction between a crustacean host and a manipulative parasite

Abstract: Parasites alter many traits of their hosts. In particular, parasites known as "manipulative" may increase their probability of transmission by inducing phenotypic alterations in their intermediate hosts. Although parasitic-induced alterations can modify species' ecological roles, the proximate factors modulating this phenomenon remain poorly known. As temperature is known to affect host-parasite associations, understanding its precise impact has become a major challenge in a context of global warming. Gammarid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 101 publications
1
14
0
Order By: Relevance
“…These results highlight that temperature is a factor influencing the movements of gammarids but that it does not influence the manipulation effects of P. laevis on G. pulex. In accordance with the study of Labaude et al (2020) in static water, we did not found an amplification of P. laevis manipulation under warmer conditions in flowing water. According to Marcogliese (2008), acanthocephalan parasites could be affected by variations in water temperature: if water temperature increases, metabolic changes induce a shorter lifespan and faster growth, with a modification in their transmission capacities.…”
Section: Effects Of Temperaturesupporting
confidence: 92%
See 3 more Smart Citations
“…These results highlight that temperature is a factor influencing the movements of gammarids but that it does not influence the manipulation effects of P. laevis on G. pulex. In accordance with the study of Labaude et al (2020) in static water, we did not found an amplification of P. laevis manipulation under warmer conditions in flowing water. According to Marcogliese (2008), acanthocephalan parasites could be affected by variations in water temperature: if water temperature increases, metabolic changes induce a shorter lifespan and faster growth, with a modification in their transmission capacities.…”
Section: Effects Of Temperaturesupporting
confidence: 92%
“…These results demonstrate that acanthocephalan extended phenotype can be modulated according to their host aquatic environment. However, Labaude et al (2020) found no effect of temperature on the manipulation behaviour of P. laevis in static water. Therefore, the way that acanthocephalan manipulate their hosts depending on such environmental constraints still requires further investigation to better understand how trophic transmission and ecosystem functioning could be affected by climate change (Marcogliese, 2001).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Among the three sub species inhabiting different climatic zones of the island, M. s. sinica found in the dry zone harbour a higher prevalence of GI parasites compared to the other two subspecies. This may be due to increase infection success and faster development in parasites in the high temperature than in relatively low temperature ranges ( Labaude et al, 2020 ). Maximum temperature is an important variable in determining soil-transmitted helminth distribution owing to effect of heat and low humidity of the soil on the embryonation, development and survival of free-living infective stages ( Brooker et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%